Cities of Tomorrow - Action Today. URBACT II Capitalisation. Key messages. - Soto, Paul (My University, 2013)
Dieser Bericht fasst die wichtigsten Punkte der vorangegangen Berichte zusammen: From Crisis to Choice: Re-Imagining the Future in Shrinking Cities / More Jobs: Better Cities - A Framework for City Action on Jobs / Supporting Urban Youth Through Social Innovation: Stronger Together / Against Divided Cities in Europe / How Cities Can Motivate Mobility Mindsets / Building Energy Efficiency in European Cities.

This report highlights some of the main points previous six reports: From Crisis to Choice: Re-Imagining the Future in Shrinking Cities / More Jobs: Better Cities - A Framework for City Action on Jobs / Supporting Urban Youth Through Social Innovation: Stronger Together / Against Divided Cities in Europe / How Cities Can Motivate Mobility Mindsets / Building Energy Efficiency in European Cities.
Keywords: Stadtentwicklungsplanung; Stadterneuerung; Stadtsoziologie; Bevölkerungsentwicklung; Arbeitsmarkt; Jugend; Mobilität; Umweltschutz